ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI CREDIT SPREADS OBLIGASI DI INDONESIA PERIODE 2008-2011 - Andriana, Putri; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to analyze the influence of stock market return volatility, GDP, default probability, and liquidity on credit spreads in Indonesia during period quarter I 2008 to quarter IV 2011. Credit spreads is the result of the difference between the yield to maturity on corporate bonds and the yield to maturity on government bonds with the same marurities.This study uses secondary data from Indonesia Stock Exchange, Indonesia Bond Market Directory, and Statistics Indonesia which involves 14 samples of non-finance corporate bonds traded during 2008-2011. This study uses panel regression method with random effect model selected by the result of Chow test and Hausman test.The result of this study showed that stock market return volatility and GDP have negatively effect on credit spreds in Indonesia. At the same time, default probability and liquidiy did not influences on credit spreads in Indonesia. From the results of panel regression showed that stock market return volatility, GDP, default probability, and liquidity can explain credit spreads in Indonesia byÂ 2.5949% and the rest is explained by other variables outside the model.